Evaluation of abdominal compression–decompression combined with chest compression CPR performed by a new device: Is the prognosis improved after this combination CPR technique? - Haishan Li; Chao Wang; Hongyuan Zhang; Fang Cheng; Shuang Zuo; Liyou Xu; Hui Chen; Xiaodong Wang (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine, 2022)
Abstract Introduction This study was designed to compare the outcomes of standard cardiopulmonary resuscitation (STD-CPR) and combined chest compression and abdominal compression–decompression cardiopulmonary resuscitation (CO-CPR) with a new device following out-of-hospital cardiac arrest (OHCA). Moreover, we investigated whether patient prognosis improved with this combination treatment. Methods This trial was a single-centre, prospective, randomized trial, and a blinded assessment of the outcomes was performed. A total of 297 consecutive patients with OHCA were initially screened, and 278 were randomized to the STD-CPR group (n = 135) or the CO-CPR group (n = 143). We compared the proportions of patients who achieved a return of spontaneous circulation (ROSC), survived to hospital admission and survived to hospital discharge. In addition, we also performed the Kaplan–Meier analysis with a log-rank test at the end of the follow-up period to compare the survival curves of the two groups. Results The differences were not statistically significant in the proportion of patients who achieved ROSC [31/135 (23.0%) versus 35/143 (24.5%)] and survived to hospital admission [28/135 (20.7%) versus 33/143 (23.1%)] between the CO-CPR group and STD-CPR group. However, there was a significant difference in the proportion of patients who survived to hospital discharge [16/135 (11.9%) versus 7/143 (4.9%)] between the two groups. Nine patients (6.7%) in the CO-CPR group and 2 patients (1.4%) in the STD group showed good neurological outcomes according to the cerebral performance category (CPC) scale score, and the difference was statistically significant (P = 0.003). The Kaplan–Meier curves showed that the patients in the CO-CPR group achieved better survival benefits than those in the STD-CPR group at the end of the follow-up period (log-rank P = 0.007). Conclusion CO-CPR was more beneficial than STD-CPR in terms of survival benefits in patients who have suffered out-of-hospital cardiac arrest. Trial registration Chinese Clinical Trial Registry, registered number: ChiCTR2100049581 . Registered 30 July 2021- Retrospectively registered. http://www.medresman.org.cn/uc/index.aspx .